Odpowiedź :
Odpowiedź:
a)
[tex]f(x)=-3x+7+[2,6]\\f(x+2)=-3x+7+6\\f(x)=-3(x-2)+13\\f(x)=-3x+6+13=-3x+19[/tex]
[tex]f(x)=-3x+7+[4,0]\\f(x+4)=-3x+7\\f(x)=-3(x-4)+7\\f(x)=-3x+19[/tex]
[tex]f(x)=-3x+7+[0,12]\\f(x)=-3x+7+12\\f(x)=-3x+19[/tex]
b)
[tex]f(x)=-3x+7+[1,9]\\f(x+1)=-3x+16\\f(x)=-3(x-1)+16\\f(x)=-3x+19[/tex]
[tex]f(x)=-3x+7+[3,3]\\f(x+3)=-3x+10\\f(x)=-3(x-3)+10\\f(x)=-3x+19[/tex]
Szczególowe wyjaśnenie:
[tex]f(x)=ax+b +[X,Y][/tex]
oznacza, że wykres funkcji f(x) przesuwa się o X w prawo i o Y do gory
[tex]f(x)=ax+b +[X,Y]\\f(x+X)=ax+b+Y\\f(x)=a(x-X)+b+Y\\f(x)=ax-aX+b+y[/tex]